Postabortion Family Planning and Associated Factors Among Women Attending Abortion Service in Dire Dawa Town Health Facilities, Eastern Ethiopia - Motuma, Venus Shewangizaw; Yadeta, Tesfaye Assebe; Alemu, Addisu; Yuya, Mohammed; Eshetu, Bajrond; Balis, Bikila; Bekana, Miressa; Merga, Bedasa Taye; Oljira, Lemessa (Frontiers in Reproductive Health, 2022)
Background: Though post-abortion family planning is part of a comprehensive package of post abortion care, break the cycle of repeated abortion, unintended pregnancies, and reduce abortion related maternal morbidity and mortality, it did not receive due attention. Therefore, this study aimed to determine the utilization of post abortion family planning and associated factors among women attending abortion service in Dire Dawa health facilities, Eastern Ethiopia. Methods: A facility-based cross-sectional study design was employed among 483 clients who sought abortion service in Dire Dawa from May 15 to June 30, 2020. A structured interviewer-administered questionnaire was used for data collection. The collected data were entered into Epi Info™ 7 and exported to SPSS version 22 for analysis. Multiple logistic regression models was fitted to identify factors associated with utilization of post-abortion family planning. Adjusted odds ratios (AORs) along with 95% CI were estimated to measure the strength of the association and declared statistical at a p-value < 0.05. Result: More than two-third, 368(77.8%), (95% CI :( 73.4-81.6%) respondents were utilized post-abortion family planning methods. Age [AOR:5.59,(95 CI:(1.5,19.7)], educational status [AOR: 7.6, (95%CI:(2.7, 21.2)], marital status [AOR:11.1,(95% CI: (4.6, 26.5)] income [AOR: 7.9, (95% CI: (3.2, 19.4)], parity ≥5 [AOR: .41, (95% CI: (.18, .92)], desire of current pregnancy [AOR: 4.2, (95% CI: (1.9, 9.3)] and ever used family planning [AOR: 4.4, (95% CI: (2.2, 8.9)] were factors significantly associated with post-abortion family planning utilization. Conclusion: In this study, post-abortion family planning utilization was relatively good. Age, educational level, marital status, income, not desire of current pregnancy, counseling and ever used family planning were factors associated with utilization of family planning.